Staging Black Fugitivity - McCormick, Stacie Selmon (Chicago : Ohio State University Press, 2019)
"Argues that contemporary black dramas use the slave past to complicate views of the history of slavery, the realities of racial progress, and black subjectivity. McCormick analyzes work by August Wilson, Suzan-Lori Parks, Tanya Barfield, Lorraine Hansberry, Lydia Diamond, Robert O'Hara, and Branden Jacobs-Jenkins, amongst others"--
Introduction: A body without a nation -- Mapping fugitivity in Black drama -- Fugitive acts -- Performing escape -- Fugitive intimacies -- Epilogue: Contemplating and complicating Black freedom.
Print version record.
JSTOR
Keywords: American drama -- African American authors -- History and criticism; Slavery in literature; African Americans -- Race identity; Racism in literature; Théâtre américain -- Auteurs noirs américains -- Histoire et critique; Esclavage dans la littérature.; Noirs américains -- Identité ethnique; Racisme dans la littérature.; LITERARY CRITICISM / General; African Americans -- Race identity; American drama -- African American authors; Racism in literature; Slavery in literature; Electronic books; Criticism, interpretation, etc